1962
DOI: 10.1063/1.1728933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystal Perfection and Polarity on Absorption Edges Seen in Bragg Diffraction

Abstract: When a single crystal is used in an x-ray spectrometer to display the continuous spectrum of an x-ray tube by Bragg diffraction, absorption edges characteristic of the atomic species in the crystal may be observed. The change in diffracted power across an edge is fundamentally due to a change in the atomic scattering, especially the imaginary part of the scattering, of the species whose edge it is. This produces a sharp anomaly in both the structure factor and the absorption factor of the reflection being used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1971
1971
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 5 publications
2
30
0
Order By: Relevance
“…As was reported by Cole & Stemple (1962), the intensity ratio between Friedel-pair reflexions of a polar crystal is given by the structure factor F or the intensity I as …”
Section: Intensity Ratio Of a Friedel Pairmentioning
confidence: 97%
“…As was reported by Cole & Stemple (1962), the intensity ratio between Friedel-pair reflexions of a polar crystal is given by the structure factor F or the intensity I as …”
Section: Intensity Ratio Of a Friedel Pairmentioning
confidence: 97%
“…Cole and Stemple (1962) studied the Bijvoet-pair reflections in the neighbourhood of the absorption edge and found that the ratio of intensities is independent of the defect state of the crystal and applies equally to ideally perfect as well as ideally imperfect crystals. Fig.…”
Section: (D) Diffracted Intensity Techniquesmentioning
confidence: 99%
“…The first is that it relies on the accurate measurement of the intensity of the diffracted beam and the conclusion by Cole and Stemple (1962) concerning the independence of intensity ratio on crystalline perfection. Other factors such as primary and secondary extinction also present difficulties to those making an accurate measurement of the intensities of the diffracted beams.…”
Section: (D) Diffracted Intensity Techniquesmentioning
confidence: 99%
“…Only recently, the latter problem has been successfully overcome by the best use of an SSD (solid-state detector) incorporated in a two-circle diffractometer (Fukamachi, Hosoya, Okunuki, Matsudo & Sakamaki, 1977), with which system the integrated intensities were feasibly measured for the weak high-angle reflexions in the energy-dispersive mode with a better SIN ratio and energy resolution than in the previous work (Cole & Stemple, 1962), in the energy region very near the absorption edge (Fukamachi, Hosoya & Okunuki, 1976a, referred to as paper I). The energy dependence of the intensity thus obtained near the edge has been explained by the dynamical theory taking account of the absorption, as already published (paper I), and accordingly the intensity ratio of the Friedel-pair reflexions has also been explained (Fukamachi, Hosoya & Okunuki, 1976b, referred to as paper II).…”
Section: Introductionmentioning
confidence: 99%